GAMBARAN PERILAKU MASYARAKAT TENTANG VAKSIN COVID-19 - Andalia Roza; Depi Anjelina (Jurnal Ilmu Kesehatan Abdurrab, 2024)
Behavior is the result of all kinds of experiences and human interactions with the environment that are manifested inthe form of knowledge, attitudes, actions. The purpose of this study was to describe the knowledge, attitudes, and actionsof the community about the covid-19 vaccine in the village of Pulau Birandang Rt 002/Rw 002, Kampa sub-district in2022. This type of research is descriptive quantitative. The population in this study is the people of the island ofBirandang rt 002/rw 002 as many as 150 people. Samples were taken by total sampling technique. The research instrument used a questionnaire consisting of 21 questions. Data analysis used univariate analysis. From theresults of this study, people's knowledge in the good category is 87.3%. The attitude of the community in covid-19vaccine has a positive attitude, namely 52%. Community action in covid-19 vaccine is 64%. Suggestion :It is hoped thatthe public can increase their knowledge of covid-19 vaccine in order to minimize the risk and prevent the occurrence ofthe virus.